The Metropolitan Museum of Art : spectacular masks to pop up, pull out, and put on. - Metropolitan Museum of Art (New York, N.Y.) (New York : Metropolitan Museum of Art : DK Pub., 1997)
Presents a variety of masks from the collections of the Metropolitan Museum of Art. Each mask can be popped out of the book, worn, and returned to the book.
"A DK Ink book"--Back cover.
Cover title.
Keywords: Metropolitan Museum of Art (New York, N.Y.) -- Juvenile literature; Metropolitan Museum of Art (New York, N.Y.).; Masks -- Juvenile literature; Masks; Toy and movable books -- Specimens; Toy and movable books